High Sensitivity of Lake Hypoxia to Air Temperatures, Winds, and Nutrient Loading: Insights From a 3‐D Lake Model. Issue 12 (14th December 2020) - Bocaniov, Serghei A.; Lamb, Kevin G.; Liu, Wentao; Rao, Yerubandi R.; Smith, Ralph E. H.
Abstract: A three‐dimensional hydrodynamic‐ecological model is applied to Lake Erie to predict the response of dissolved oxygen (DO) to independent changes in air temperature, wind speeds and total phosphorus (TP) loading. Warmer temperatures and lower wind speeds increased the size and duration of hypoxic and anoxic regions by lengthening the stratified period. Decreased wind speed increased hypolimnion thickness while decreasing its temperature and DO consumption rate. Decreased TP loading improved DO conditions with a reduction of 75% effectively abolishing hypoxia. Anoxia was more sensitive to air temperature, wind, and nutrient changes than was hypoxia. New metrics that capture the spatial and temporal dimensions of low DO conditions were more sensitive than the commonly cited maximum areas of hypoxia or anoxia. Over most of the relevant range of forcing factors, the simple and first‐order effect of a 1°C temperature change was equivalent to a 10–14% change in TP loads, while a 1% change in wind speed was equivalent to a 2–3% change in TP loads. Reduced ice cover in warmer climates will likely increase air temperature effects even further. Key Points: 3‐D ecosystem modeling of a Great Lake showed high sensitivity of hypoxia to climatic air temperature and wind speed variations Anoxia (<1 mg O2 /L) was even more sensitive than hypoxia (<2 mg O2 /L) Effects of future temperatures and winds may imply a need for further nutrient reduction approaching 50% beyond current remediation targets